Retinoic acid elicits a coordinated expression of gut homing markers on T lymphocytes of Zambian men receiving oral Vivotif, but not Rotarix, Dukoral or OPVERO vaccines - Mwanza-Lisulo, Mpala (Vaccine, 2018)
All-trans retinoic acid (ATRA) up-regulates, in laboratory animals, the expression of the gut homing markers α4β7 integrin and CCR9 on lymphocytes, increasing their gut tropism. Here, we show that, in healthy adult volunteers, ATRA induced an increase of these gut homing markers on T cells in vivo in a time dependent manner. The coordinated increase of α4β7 and CCR9 by ATRA was seen in 57% (12/21) of volunteers and only when given together with an oral Vivotif vaccine. When this coordinated response to ATRA and Vivotif vaccine was present, it was strongly correlated with the gut immunoglobulin A (IgA) specific response to vaccine LPS (ρ = 0.82; P = 0.02). Using RNA-Seq analysis of whole blood transcription, patients receiving ATRA and Vivotif in conjunction showed transcriptomic changes in immune-related pathways, particularly including interferon α/β signaling pathway, membrane-ECM interactions and immune hubs. These results suggest that exogenous ATRA can be used to manipulate responses to a subclass of oral vaccines, so far limited to a live attenuated Vivotif vaccine.